Adoption of sustainable agricultural practices by traditional rice growers - Bonny, Binoo P.; Vijayaragavan, K. (Journal of Tropical Agriculture, 2006)
Farmer sustainability index (FSI) was developed to measure the adoption of sustainable practices by traditional rice growers of Kuttanad agro-ecosystem in Kerala. Based on the mean FSI scores of each group, the groups were named as conventional and sustainable. The results indicate a wide range between the mean FSI scores of conventional (23.95) and sustainable (70.06) adopter categories. The conventional and sustainable adopter categories maintained significantly distinct positions on all selected practices and also on the overall total FSI scores. It proved that the conventional and sustainable groups acted differently on all production practices in concordance with their technological allegiance.